MEASURING MILLENNIALS' BEHAVIOR IN AVOIDING ADVERTISING ON YOUTUBE CHANNELS: A PUBLIC SERVICE ADVERTISEMENT REGARDING COVID-19 - Yulita, Henilia; Yudhi, Lim (Universitas Bunda Mulia, 2022)
The pandemic of COVID-19 has had an impact on society and business. This includes the impact on people's information, product, and service consumption patterns. People spend more time at home because of social restrictions imposed to limit the spread of COVID-19. This is also gradually indicating opportunities for industry participants to deliver advertisements for their products or services via online media. The purpose of this study is to identify and analyze the determinants of attitudes toward advertising using ad content and advertising value. As an analytical tool, this quantitative study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with SMART PLS. This study included 150 millennial YouTube users as participants. According to the findings of this study, ad content has a significant impact on advertising value. Furthermore, this study explains how ad content influences consumer attitudes toward advertising. The study's next finding explains that advertising value has no effect on attitudes toward advertising. This study explains, on the indirect effect, that advertising value does not mediate the relationship between ad content and attitude toward advertising. Other variables, such as advertising provider credibility and public saturation of COVID-19, can be suggested for future research.